Foreign Direct Investment: Impact on Indian Economy - Saxena, Dr Kavita (Innovative Research Thoughts, 2017)
When a foreign investor invests in a business operating in a different economy than their own, they are known as "foreign direct investment" (FDI), or foreign investment. All long-term and short-term capital that a company has as evidenced in its balance of payments is included in this total figure. Participation in management, joint venture, transfer of technology and experience are all common ways in which it may be done. Foreign Direct Investment (FDI) is divided into two categories: "Inward Foreign Direct Investment" and "Outward Foreign Direct Investment," both of which lead to a net FDI inflow (positive or negative) and "Stock of Foreign Direct Investment." Investing directly does not include stock purchases. Foreign direct investment (FDI) is a kind of international factor movement that occurs. An investment in a foreign firm, often one that is owned by the foreign corporation.